The Positive Impact of Football Schools on Students’ Character Development: A Case Study at SSB Bintang Kejora Masbagik (Ages 14-15 Years) - Jamaludin, Jamaludin; Wijaya, Lalu Sapta (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to analyze the positive impact of football training programs on the character development of students aged 14-15 at Sekolah Sepak Bola (SSB) Bintang Kejora Masbagik. Character development in adolescents is a crucial aspect of shaping their identity and values, which will guide them in the future. Football, as a team sport, holds significant potential in instilling values such as discipline, sportsmanship, leadership, and cooperation, which are essential for character development. This research uses a qualitative approach with a case study design, collecting data through interviews with coaches and students, character questionnaires, and direct observation. The questionnaire results show that 64% of students fall into the moderate character development category, 21% into the low category, and 14% into the high category. While most students show progress, there is still room for further improvement in character development. Interviews with the coach revealed that the main challenge is maintaining a balance between technical skill development and consistent character building in every training session. The findings suggest that while the program has a positive impact, further efforts are needed to strengthen character development more evenly among students. This study provides valuable insights for SSB managers and other sports organizations to design more effective training programs for adolescent character development.